Exploration of Phytochemical and Morphological Profile of Melastoma malabathricum from Central Kalimantan as a Tropical Plant with Therapeutic Value - Noor Hujjatusnaini; Dita Sevtia; Ridha Nirmalasari (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
This study aimed to explore the morphological characteristics and phytochemical content of Melastoma malabathricum, a tropical plant native to Central Kalimantan, recognized for its therapeutic potential. Sampling was conducted purposively in its natural habitat, followed by morphological description and preliminary phytochemical tests to identify secondary metabolites using standard phytochemical screening methods (tube test). The results revealed that M. malabathricum exhibits distinctive morphological features in both vegetative and reproductive organs, including woody stems with prominent branches, single elliptical leaves with three pinnate veins and a hairy underside, bright purple flowers with prominent petals, small, round fruits that turn purple-black when ripe, and taproots with numerous branches. Phytochemical tests revealed the presence of flavonoids, tannins, saponins, and alkaloids, supporting the plant's pharmacological potential. Traditionally, this species has been used as a wound healer, anti-inflammatory agent, and antimicrobial remedy. M. malabathricum shows promise as a valuable source of natural bioactive compounds, facilitating research into the development of modern herbal medicines. These findings confirm that M. malabathricum not only exhibits unique morphological characteristics typical of tropical habitats but also holds significant potential for advancement in health and pharmacology. Due to its diverse secondary metabolite profile, this plant is an excellent candidate for phytopharmaceutical raw materials, warranting further research focused on isolating active compounds and evaluating their biological activities both in vitro and in vivo.